2011
DOI: 10.1158/2159-8290.cd-11-0289
|View full text |Cite
|
Sign up to set email alerts
|

Anti-MET Targeted Therapy Has Come of Age: The First Durable Complete Response with MetMAb in Metastatic Gastric Cancer

Abstract: The MET/hepatocyte growth factor (HGF) signaling pathway plays important roles in oncogenesis and tumor progression in a variety of human cancers. MET/HGF drives an invasive signaling program that can be dysregulated in human cancers through a number of activating mechanisms, including mutations, overexpression, amplification, alternative splicing, and HGF ligand–induced autocrine/paracrine loop signaling. As a testimony of MET-targeting therapeutics is beginning to come to clinical fruition, Catenacci and col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…In addition, about 20% of human gastric cancer cell lines exhibit MET amplification with a corresponding MET addiction phenotype, rendering these tumor cells extremely sensitive to MET inhibition (10). Accordingly, MET is considered to be a prognostic marker and at the same time an important therapeutic target for locally advanced or metastatic gastric cancers (11,12). Currently, several anti-MET antibodies and small-molecule MET inhibitors are undergoing phase I and phase II clinical trials in different types of solid tumors, including gastric cancer (e.g., NCT02435108, NCT01468922, NCT00725712, NCT02002416), with only a modest benefit in otherwise unselected patient populations (13).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, about 20% of human gastric cancer cell lines exhibit MET amplification with a corresponding MET addiction phenotype, rendering these tumor cells extremely sensitive to MET inhibition (10). Accordingly, MET is considered to be a prognostic marker and at the same time an important therapeutic target for locally advanced or metastatic gastric cancers (11,12). Currently, several anti-MET antibodies and small-molecule MET inhibitors are undergoing phase I and phase II clinical trials in different types of solid tumors, including gastric cancer (e.g., NCT02435108, NCT01468922, NCT00725712, NCT02002416), with only a modest benefit in otherwise unselected patient populations (13).…”
Section: Introductionmentioning
confidence: 99%
“…Conventional antibodies can also induce c-Met dimerization, therefore acting as agonists. One-armed antibody-like molecules, such as onartuzumab, do not cross-link c-Met and can inhibit its HGF-induced signaling (Feng and Ma 2011 ;Merchant et al 2013 ). However, such monovalent antibodies can lose up to 100-fold in bioactivity due to the loss of avidity in their binding, making restoration of bivalent targeting benefi cial (Fig.…”
Section: Case Studies Of Antibody-like Molecules Designed For Superiomentioning
confidence: 99%
“…In a Phase I study dose-escalation study of onartuzumab in patients with various locally advanced or metastatic solid tumors, a sustained complete response (>2 years) was noted in a patient with chemorefractory GEC with hepatic metastases [49, 50]. Interestingly, serial correlative blood and tissue studies in this patient showed MET gene polysomy, moderate MET expression by IHC and a remarkably high baseline serum HGF level.…”
Section: Introductionmentioning
confidence: 99%